Preparation method of PET foamed composite core material for fan blade
Through the combination of a dedicated batch FPET Block production system and composite prepreg belt, the problem of low production efficiency of PET rigid closed-cell foam core materials is solved, and high-efficiency production of high-quality PET foam composite core materials for fan blades is achieved, reducing production costs and supporting the development of large megawatt-type wind power generation products.
Patent Information
- Application Number
- CN202411857139.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-18
AI Technical Summary
The production efficiency of existing PET rigid closed-cell foam core materials is low, resulting in high total production cost of fan blades, which cannot meet the development needs of large megawatt models of wind power generation products.
The PET foam composite core material for fan blades is produced by using a special batch FPET Block production system combined with a self-designed composite belt.
It effectively improves the production efficiency of core materials, improves the impact toughness and wind pressure impact resistance of wind power blades, reduces the total production cost of fan blades, and supports the development and breakthrough of large megawatt-type wind power generation products.
Smart Images

Figure CN119636116A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of preparation of core materials for fan blades, and in particular to a method for preparing a PET foamed composite core material for fan blades. Background Art
[0002] With the advancement of wind power technology, the development of large-scale single-unit capacity in the wind power industry has become an inevitable trend. Complete machine manufacturers with large-megawatt wind power generation products will be more competitive in the future. Large-megawatt models with large single-unit capacity not only effectively improve the utilization efficiency of wind energy resources, land / sea area utilization efficiency, reduce the cost per kilowatt-hour, and improve the return on investment, but also help to improve the overall economic efficiency of wind power project investment, development and operation, and facilitate large-scale project development, thereby reducing the cost per kilowatt-hour of wind power, and facilitating the steady advancement of the grid parity policy. With the steady advancement of the grid parity policy, it is also conducive to accelerating the promotion of wind power cost reduction and the development of large-megawatt models. The two complement each other and derive the rapid development and breakthroughs of wind power technology.
[0003] Wind turbine blades are one of the most basic and cost-intensive parts of wind turbines, and their quality is directly related to equipment safety and power generation efficiency. The key components of wind turbine blades include the main beam, trailing edge beam, web, and shell. The shell is composed of upper and lower skins and a core material filled between the upper and lower skins; the upper and lower skins are made of polymer materials reinforced with glass fiber or carbon fiber; the core material includes balsa wood and rigid closed-cell foam, and the rigid closed-cell foam includes PET foam material and PVC foam material; the balsa wood includes red cardia poplar, European pine, birch, beech, Douglas fir, etc. However, due to the cost of wood, the non-recyclability of wood, the heavy weight of the prepared wind turbine blades, and the deviation of mechanical properties, the core material in the current mainstream wind turbine blades is mainly PET rigid closed-cell foam.
[0004] PET rigid closed-cell foam core is a PET foam sheet made by extrusion foaming process. Due to the working environment requirements of wind turbine blades, PET rigid closed-cell foam core has higher shear and compressive strength requirements. The shear and compressive strength of PET foam sheet made by extrusion foaming is better in the y-axis direction, but the shear and compressive strength deviation in the x-axis direction, i.e. the resin extrusion direction, makes it unable to meet the requirements of the development of large-scale single-unit capacity in the wind power industry.
[0005] Currently, the preparation process of PET rigid closed-cell foam core material includes the following steps: S1. First, a PET foam substrate is prepared by a conventional extrusion foaming process; S2. Multiple PET foam substrates are stacked along the y-axis direction to form an FPET Block, and adjacent PET foam substrates are hot-pressed and fixedly connected one by one through an intermittent hot plate pressing process; S3. The obtained FPET Block is vertically cut and leveled along the y-axis direction to obtain a PET rigid closed-cell foam core material, and the obtained PET rigid closed-cell foam core material is slotted, punched, edge-cut and leveled, and polished according to the design requirements of the fan blade to finally obtain a finished PET foam core material.
[0006] refer to Figure 1In the preparation of FPET Block in the preparation process S2 of the PET rigid closed-cell foam core material, the intermittent hot plate pressing process is specifically as follows: a single PET foam substrate is clamped by the robot A100, and another PET foam substrate is fixed on the processing table 101 which can horizontally move the PET foam substrate, and the robot B102 installed on the lead screw of the processing table 101 clamps the PET foam substrate. The PET foam substrate clamped by the robot A100 coincides with the horizontal projection of the PET foam substrate on the processing table 101, that is, the two surfaces can be completely stacked. An electric heating plate 103 is arranged between the PET foam substrate clamped by the robot A100 and another PET foam substrate on the processing table 101 that slides to the side closest to the PET foam substrate clamped by the robot A100. The surface size of the electric heating plate 103 is equal to the upper and lower surface sizes of the PET foam substrate, and the electric heating plate 103 can be displaced and slid between the two PET foam substrates parallel to the PET foam substrate. When the electric heating plate 103 is required to be hot-pressed and fixed, the electric heating plate 103 is slid parallel to the PET foam substrate and placed between the two PET foam substrates until the horizontal projection of the electric heating plate overlaps between the two PET foam substrates, and then the electric heating plate 103 is turned on to perform heat-melting treatment on the surfaces of the two PET foam substrates. After the surface heat-melting treatment is completed, the electric heating plate 103 slides parallel to the outside of the two PET foam substrates through the track. At this time, the PET foam substrate clamped by the robot A100 coincides with the horizontal projection of the PET foam substrate clamped by the robot B102 on the processing table 101. The clamped PE is moved by the robot A100 and applied with a pressure of 20-40N. The hot melt treated surface of the T foam substrate is bonded to the hot melt treated surface of another PET foam substrate on the processing table 101, and the mechanical arm A100 continues to bond for at least 5 minutes under the pressure of the mechanical arm A100, so that the two PET foam substrates can be hot-pressed and bonded together to obtain a two-fold PET foam board, and the mechanical arm clamp A100 releases the two-fold PET foam board, and the mechanical arm clamp B102 clamps the two-fold PET foam board and places it on the processing table 101, and then the mechanical arm A100 clamps another new PET foam substrate and repeats the above hot pressing and bonding operation to obtain a three-fold PET foam board, and the intermittent hot plate pressing process is used to obtain a four-fold PET foam board, a five-fold PET foam board... until a standard FPET Block is obtained, and then the standard FPET Block on the processing table is moved to produce the next standard FPET Block. With respect to the FPETBlock preparation process in the above-mentioned related art, the inventor found that there are the following defects: the production efficiency of FPET Block is low, resulting in a high total cost of wind turbine blade production, which is not conducive to the development and breakthrough of large-megawatt wind power generation products. Summary of the invention
[0007] In order to solve the problem that the production efficiency of PET foam composite core materials in the prior art is relatively low, which affects the total production cost of wind turbine blades, the present application provides a method for preparing PET foam composite core materials for wind turbine blades.
[0008] The present application provides a method for preparing a PET foam composite core material for a fan blade, which is achieved through the following technical solutions: A method for preparing a PET foam composite core material for a fan blade, comprising the following steps: Step 1: Preparation of PET foam substrate and composite prepreg coil: The composite prepreg tape coil comprises a first release paper, a plurality of composite prepreg tapes, and a second release paper, wherein the composite prepreg tape is composited between the first release paper and the second release paper; The composite prepreg tape comprises a first PET layer, a TPEE toughened and reinforced PET composite layer, and a second PET layer, the thickness of the first PET layer and the second PET layer are both 25-200 μm; the thickness of the TPEE toughened and reinforced PET composite layer is 50-2000 μm, and the TPEE toughened and reinforced PET composite layer is filled with a fiber skeleton, and the fiber skeleton is 0° fiber and / or 90° fiber and / or plain woven fiber mesh; The 0° fiber includes at least one of glass fiber, carbon fiber, basalt fiber, aramid fiber, and ultra-high molecular weight polyethylene fiber distributed along the X-axis direction; The 90° fiber includes at least one of glass fiber, carbon fiber, basalt fiber, aramid fiber, and ultra-high molecular weight polyethylene fiber distributed along the Y-axis direction; The warp threads in the plain woven fiber mesh cloth include at least one of glass fiber, carbon fiber, basalt fiber, aramid fiber, and ultra-high molecular weight polyethylene fiber, and the weft threads in the plain woven fiber mesh cloth include at least one of glass fiber, carbon fiber, basalt fiber, aramid fiber, and ultra-high molecular weight polyethylene fiber; Step 2: First, a composite prepreg tape is hot-pressed on a PET foam substrate through a dedicated batch FPET Block production system, and then another PET foam substrate is hot-pressed on the composite prepreg tape, and the two PET foam substrates are hot-pressed and composited through the composite prepreg tape to form a double-stacked PET foam board; Step 3, the two stacked PET foam sheets are laminated at least sequentially from bottom to bottom on the composite prepreg tape / PET foam substrate / …… / PET foam substrate / composite prepreg tape / PET foam substrate to form n+1 stacked PET foam sheets, i.e., semi-finished FPET Block; Step 4, heat-treating the semi-finished FPET Block to obtain a finished standard FPET Block; Step 5: The standard FPET Block is vertically cut along the y-axis direction to obtain a PET foam composite core material substrate, and the obtained PET foam composite core material substrate is grooved, punched, edge cut, flattened, and polished to obtain a finished PET foam composite core material.
[0009] Preferably, in step 4, the semi-finished FPET Block is heat treated, and the heat treatment parameters are as follows: heat treatment at 80-90° C. for 200-400 seconds, and cooling to room temperature to obtain a finished standard FPET Block.
[0010] The present invention achieves the purpose of mass and continuous production of high-quality PET foam composite core materials for wind turbine blades through a dedicated mass FPET Block production system combined with a self-designed composite prepreg tape, effectively improving the production efficiency of the core material while improving the impact toughness and wind pressure impact resistance of wind turbine blades, reducing the total production cost of wind turbine blades, and facilitating the development and breakthrough of large-megawatt wind power generation products.
[0011] Preferably, the preparation method of the composite prepreg coil in step 1 is as follows: S1, preparation of TPEE toughened and reinforced PET composite film; the TPEE toughened and reinforced PET composite layer is prepared by extrusion melting, casting, stretching and cooling of TPEE toughened and reinforced PET masterbatch; S2, preparation of composite prepreg tape: first fix the fiber skeleton in a forming mold, then apply the TPEE toughened and reinforced PET composite film to the upper and lower surfaces of the fiber skeleton respectively, and obtain the TPEE toughened and reinforced PET composite sheet containing the fiber skeleton by hot pressing and compounding, that is, the TPEE toughened and reinforced PET composite layer, and then cover the first PET film on one surface of the TPEE toughened and reinforced PET composite sheet, and cover the second PET film on the other surface of the TPEE toughened and reinforced PET composite sheet, and obtain the composite prepreg tape containing the fiber skeleton by hot pressing and compounding, cut, trim, and set aside; S3, preparation of composite prepreg tape roll: firstly compound a plurality of composite prepreg tapes on a second release paper, with the intervals between adjacent composite prepreg tapes on the second release paper being equal, and then compound the first release paper on the surface of the composite prepreg tape facing away from the composite prepreg tape, and then roll up to obtain a finished composite prepreg tape roll.
[0012] The preparation method of the composite prepreg coil provided in the present invention is relatively simple. It can be selected to form a type A composite prepreg by hot pressing at normal pressure, or it can be selected to place the forming mold in a vacuum autoclave for vacuum hot pressing to form a type B composite prepreg. Type A composite prepreg has met the production needs of industrialization, while type B composite prepreg is developed and designed to meet the mechanical property requirements of PET foam composite core materials for high-performance wind turbine blades. The mechanical properties of the PET foam composite core material prepared with type B composite prepreg are relatively good, but the production cost of the corresponding type B composite prepreg is relatively high.
[0013] The mass production of composite prepreg coils reduces the overall production cost of composite prepregs, thereby reducing the total production cost of wind turbine blades, which is conducive to the development and breakthrough of large-megawatt wind power products.
[0014] Preferably, the TPEE toughened and reinforced PET masterbatch is made of the following raw materials in percentage by mass: 25-40% TPEE resin, 3-6% compatibilizer, 0.5-3% PET adhesion promoter, 0.8-2% antioxidant, 0.5-1.0% anti-ultraviolet agent, 0.5-1.0% lubricant, 0.5-1.0% release agent, 0-15% filler, and the balance is PET resin; The TPEE resin has a melting temperature of 195-220° C., a bending elastic modulus ≥180 MPa, a tensile strength ≥24 MPa, and a Shore hardness of 45-55D; The compatibilizer is at least one of W5D polyester compatibilizer, W5F polyester compatibilizer, W5A polyester compatibilizer, and cyclic maleic anhydride grafted product; The PET adhesion promoter is at least one of Y-1900-1PET adhesion promoter, F-1 PET adhesion promoter, ADK adhesion promoter, 9041 adhesion promoter, HYCM-7555 adhesion promoter, epoxy silane, amino silane, isocyanate silane, and methacryloxy silane; The antioxidant is an organic phosphite antioxidant and / or an organic phenol antioxidant; The anti-ultraviolet agent is at least one of a benzotriazole ultraviolet absorber, an oxalic acid amide light stabilizer, a triazine light stabilizer, and a hindered amine light stabilizer; The filler includes a thermally conductive filler and / or a reinforcing filler; The reinforcing filler includes at least one of calcium carbonate, barium sulfate, kaolin, montmorillonite, silicon powder, titanium dioxide, mica powder, quartz powder, shell powder, chopped carbon fiber, chopped glass fiber, and inorganic whiskers; The thermal conductive filler comprises at least one of aluminum oxide, aluminum nitride, silicon nitride, titanium nitride, boron nitride, silicon carbide, titanium carbide, and zirconium carbide, and at least one of graphene and carbon nanotubes; The PET resin is bottle-grade polyester chips, and the bottle-grade polyester chips are any one of Wankai WK801, Sanfangxiang CZ-318, Hainan Yisheng-YS-Y01, Pan Asia FY1004, and Huarun CR-8863. The preparation method of the composite prepreg tape coil can be used to industrially mass-produce low-cost and high-quality composite prepreg tape coils, thereby reducing the total production cost of the PET foam composite core material.
[0015] Preferably, the filler in the TPEE toughened and reinforced PET masterbatch consists of a thermally conductive filler and a reinforcing filler, and the thermally conductive filler forms a three-dimensional network thermally conductive structure in the TPEE toughened and reinforced PET composite film. The thermal conductivity of the TPEE toughened and reinforced PET composite film is 0.5-3.0 W / m·K.
[0016] Preferably, the first PET film and the second PET film contain thermally conductive fillers, and the thermally conductive fillers form a three-dimensional network thermally conductive structure in the first PET film or the second PET film. The thermal conductivity of the first PET film and the second PET film is 0.5-3.0 W / m·K.
[0017] Preferably, the thermal conductivity of the composite prepreg tape as a whole is 0.5-3.0 W / m·K.
[0018] Preferably, the thermally conductive filler includes at least one of aluminum oxide, aluminum nitride, silicon nitride, titanium nitride, boron nitride, silicon carbide, titanium carbide, and zirconium carbide in combination with at least one of graphene and carbon nanotubes.
[0019] Further preferably, the thermally conductive filler in the TPEE toughened and reinforced PET masterbatch is composed of ultrafine spherical alumina and carbon nanotubes in a mass ratio of (18-19): (1-2); the reinforcing filler in the TPEE toughened and reinforced PET masterbatch is composed of ultrafine calcium carbonate and chopped glass fiber in a mass ratio of (4-7): 1; or the reinforcing filler in the TPEE toughened and reinforced PET masterbatch is composed of ultrafine calcium carbonate, chopped glass fiber and inorganic whisker in a mass ratio of (14-17): (2-4): 1; the thermally conductive filler in the first PET film and the second PET film is also composed of ultrafine spherical alumina and carbon nanotubes in a mass ratio of (18-19): (1-2).
[0020] The composite prepreg tape with certain thermal conductivity designed in the present application realizes rapid heat transfer, facilitates relatively rapid hot pressing compounding, improves the hot pressing compounding efficiency of the standard FPET Block, and thus helps to improve the production efficiency of the core material; in addition, the addition of thermally conductive fillers also realizes the toughening and reinforcement of the composite prepreg tape, thereby improving the overall mechanical properties and impact toughness of the PET foam composite core material for wind turbine blades, which is in line with the development trend of large-scale single-unit capacity in the wind power industry.
[0021] Preferably, the TPEE toughened and reinforced PET masterbatch is made of the following raw materials in percentage by mass: 34-36% of TPEE resin LN5355HR, 4-6% of compatibilizer - W5F polyester compatibilizer, 0.8-1.2% of PET adhesion promoter 9041, 0.70-0.85% of antioxidant 1024, 0.15-0.2% of antioxidant 168, 0.70-0.80% of anti-ultraviolet agent UV-531, 0.8-1.0% of zinc stearate, 0.4-0.6% of release agent PETSPT100, 4-6% of filler, and the balance is PET resin YS-Y01; the filler is composed of 2000 mesh ultrafine calcium carbonate, chopped glass fiber and zinc oxide whisker in a mass ratio of 16:3:1.
[0022] Preferably, the TPEE toughened and reinforced PET masterbatch is made of the following raw materials in percentage by mass: 38-40% TPEE resin LN5355HR, 3.8-4% compatibilizer-W5F polyester compatibilizer, 1.4-1.5% PET adhesion promoter 9041, 0.75-0.8% antioxidant 1024, 0.15-0.2% antioxidant 168, 0.7-0.8% anti-ultraviolet agent UV-531, 0.8-1% zinc stearate. , 0.4-0.6% of release agent PETSPT100, 8-10wt% of thermal conductive filler, 2-4% of reinforcing filler, and the balance is PET resin YS-Y01; the thermal conductive filler is composed of ultrafine spherical alumina and carbon nanotubes in a mass ratio of 19:1; the reinforcing filler is composed of 2000 mesh ultrafine calcium carbonate and zinc oxide whiskers in a mass ratio of 19:1; the thermal conductivity of the TPEE toughened and reinforced PET masterbatch is 0.75-0.95W / m·K.
[0023] The TPEE toughened and reinforced PET composite layer gives the composite prepreg tape good impact toughness and cushioning and shock absorbing properties, meeting the flexible design requirements of the composite prepreg tape, and can improve the overall mechanical properties and impact toughness of the PET foam composite core material for wind turbine blades, which is in line with the development trend of large-scale single-unit capacity in the wind power industry.
[0024] Preferably, the preparation method of the TPEE toughened and reinforced PET composite film is as follows: S1. Evenly mix the accurately measured TPEE resin, compatibilizer, PET adhesion promoter, antioxidant, UV resistant agent, lubricant, release agent, filler and PET resin and place them in a screw extruder for melt extrusion, wire drawing, cooling, granulation and drying to obtain TPEE toughened and reinforced PET masterbatch; S2. The TPEE toughened and reinforced PET masterbatch is placed in a screw extruder for melt extrusion, casting, biaxial stretching, shaping, and cooling to obtain a TPEE toughened and reinforced PET composite unit film. The film thickness of the obtained TPEE toughened and reinforced PET composite unit film can be obtained by adjusting the transverse stretching coefficient and the longitudinal stretching coefficient in the biaxial stretching parameters to obtain a TPEE toughened and reinforced PET composite film with a thickness of 50-2000μm.
[0025] The preparation method of the TPEE toughened and reinforced PET composite film can be used for industrial batch production of TPEE toughened and reinforced PET composite films, thereby reducing the production cost of composite prepreg coils, and further reducing the total production cost of PET foamed composite core materials.
[0026] The special batch FPETBlock production system used in the preparation method of the PET foam composite core material for wind turbine blades in the present invention is adapted to the continuous production of the standard FPET Block. The special batch FPET Block production system includes a plurality of PET foam substrate hot pressing subsystems and an FPET Block heat treatment subsystem. The PET foam substrate hot pressing subsystem is used to hot press and compound the PET foam substrate / composite prepreg tape / PET foam substrate to form a two-layer PET foam board or to hot press and compound n-layer PET foam boards / composite prepreg tape / PET foam substrate to form n+1-layer PET foam boards. The semi-finished product FPET Block is obtained by batch and continuous production through the plurality of PET foam substrate hot pressing subsystems. The obtained semi-finished product FPETBlock is heat treated by the FPET Block heat treatment subsystem to obtain the finished standard FPET Block. The number of the PET foam substrate hot pressing subsystems determines the number of PET foam substrates hot pressed and compounded in the finished standard FPET Block, and the number of PET foam substrates hot pressed and compounded in the finished standard FPETBlock determines the length of the finished PET foam composite core material.
[0027] Preferably, the bonding strength between the composite prepreg tape and the first release paper is smaller than the bonding strength between the second release paper and the composite prepreg tape, a non-silicone oil covering area is formed on the surface where the second release paper contacts the composite prepreg tape, and the bonding strength between the non-silicone oil covering area of the second release paper and the composite prepreg tape is greater than the bonding strength between the silicone oil covering area of the second release paper and the composite prepreg tape; the composite prepreg tape is compounded between the first release paper and the second release paper; the spacing between adjacent composite prepreg tapes is equal to the spacing between two PET foam substrates transported on the conveying belt assembly in the PET foam substrate hot pressing subsystem, so as to ensure the continuous hot pressing operation of the PET foam substrate hot pressing subsystem; the spacing between the two PET foam substrates is 1-3m.
[0028] The present invention realizes the purpose of mass and continuous production of high-quality PET foam composite core materials for wind blades through the independently designed special batch FPET Block production system combined with composite prepreg coils, effectively improving the production efficiency of the core material and reducing the total production cost of wind blades.
[0029] The structure of the dedicated batch FPET Block production system is relatively simple, and the operation difficulty is relatively low, which is conducive to reducing labor training costs and maintenance costs. In addition, the hot pressing composite parameters of the dedicated batch FPET Block production system are easy to control, thereby ensuring the quality and yield of the prepared PET foam composite core material, optimizing the production cost of the PET foam composite core material, and helping to reduce the total production cost of wind turbine blades.
[0030] In summary, this application has the following advantages: 1. The preparation method provided by the present invention can mass-produce high-quality PET foam composite core materials for wind turbine blades continuously, effectively improving the production efficiency of the core materials, reducing the production cost of wind turbine blades, and facilitating the development of large-megawatt wind power generation products.
[0031] 2. The present invention realizes the purpose of batch and continuous production of high-quality PET foam composite core materials for wind turbine blades by combining a self-designed dedicated batch FPET Block production system with a composite prepreg tape, thereby effectively improving production capacity.
[0032] 3. The structure of the dedicated batch FPET Block production system of the present invention is relatively simple and easy to operate, which is beneficial to reducing labor training costs and maintenance costs.
[0033] 4. The hot pressing composite parameters of the dedicated batch FPET Block production system of the present invention are easy to control, and the quality of the prepared PET foam composite core material is relatively stable and the yield rate is relatively high, that is, the production cost of the PET foam composite core material is relatively reduced, which is ultimately conducive to the optimization design of the total production cost of the wind turbine blades. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 It is a schematic diagram of the production process of FPET Block in the prior art.
[0035] Figure 2 1 is a diagram showing three composite structures of the composite prepreg tape and the PET foam substrate in the embodiment.
[0036] Figure 3 1 is a diagram showing the structure of the composite prepreg coil in the embodiment.
[0037] Figure 4 Schematic diagram of the structure of the production equipment for composite prepreg coil in the embodiment.
[0038] Figure 5 It is a simplified diagram of the production process of the dedicated batch FPET Block production system in the embodiment.
[0039] Figure 6 It is a production detail display diagram of the dedicated batch FPET Block production system in the embodiment.
[0040] Figure 7 Schematic diagram of the structure of the FPET Block heat treatment subsystem in the embodiment.
[0041] Figure 8 Schematic diagram of the structure of the laser scanning heating component in the embodiment.
[0042] Fig. 9 Schematic diagram of the structure of the FPET Block heat treatment subsystem in the embodiment.
[0043] Fig.10 Schematic diagram of the structure of the PET foam substrate handling assembly in the embodiment.
[0044] Fig.11 Schematic diagram of the structure of the clamping jaw assembly of the PET foam substrate handling assembly in the embodiment.
[0045] In the figure, 1, the first PET layer; 10, the composite prepreg tape; 100, the robot arm A; 101, the processing table; 102, the robot arm B; 103, the electric heating plate; 2, the TPEE toughened and reinforced PET composite layer; 3, the second PET layer; 4, the PET foam substrate hot pressing subsystem; 40, the FPET Block heat treatment subsystem; 401, the conveyor belt assembly; 402, the oven; 403, the hot pressing roller group; 404, the hot pressing roller; 41, the conveyor belt assembly; 42, the composite prepreg tape coil storage roller; 43, the first release paper peeling roller; 44, the first hot pressing roller; 45, the first release paper recovery roller; 46, the laser scanning and heating assembly; 461, the first screw rod; 462, the screw drive motor; 463, the laser transmitter A; 47, second hot pressing roller; 48, second release paper recovery roller; 49, third hot pressing roller; 5, leveling roller; 6, PET foam substrate handling assembly; 61, support base; 62, crossbar assembly; 620, electric push cylinder A; 621, support slide bar; 622, slide screw; 623, stepping motor; 63, clamping claw assembly; 631, connecting piece; 632, main pipe A; 633, slide pipe A; 6331, limit ring; 634, first cylinder; 635, platform plate; 636, second cylinder; 637, suction plate; 6371, laser transmitter B; 6372, rubber pad; 638, gripping claw arm; 6381, main pipe B; 6382, sliding pipe B; 6383, limiting ring; 6384, third cylinder; 639, fixture; 6391, rectangular bearing block; 6392, fourth cylinder; 6393, positioning cone; 7. Second release paper receiving roller; 71. First guide roller; 72. First flattening roller group; 73. Composite prepreg tape hot pressing assembly; 731. First hot pressing plate; 732. Second hot pressing plate; 74. Second flattening roller group; 75. First release paper receiving roller; 76. Second guide roller; 77. First hot pressing roller; 78. Second hot pressing roller; 79. Composite prepreg tape roll receiving roller; 8. First release paper; 9. Second release paper. DETAILED DESCRIPTION
[0046] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples and comparative examples.
[0047] Embodiment: A method for preparing a PET foam composite core material for a fan blade comprises the following steps: Step 1, preparation of PET foam substrate: 100 parts of PET chips are dried and mixed with 2 parts of nucleating agent (LicomontNAV101) and 5 parts of chain extender 6059, and then are uniformly fed into a twin-screw extruder. After being melted and plasticized at 275°C, PET undergoes a chain extension and viscosity-increasing reaction in the twin-screw extruder. A mixed gas of cyclopentane / carbon dioxide (volume ratio 1:1) is introduced and uniformly mixed at a pressure of 10-15 MPa. After the outlet pressure is reduced, the gas is precipitated to obtain PET foam, which is then cooled and cut into a fixed-size substrate. The standard size of the obtained PET foam substrate is 1200 mm long, 1000 mm wide, and 50 mm high. At the same time, the composite prepreg coil is prepared; See also Figure 2-3 The composite prepreg tape coil comprises a first release paper 8, a plurality of composite prepreg tapes 10, and a second release paper 9, wherein the composite prepreg tape 10 is composited between the first release paper 8 and the second release paper 9. The composite prepreg tape comprises a first PET layer 1, a TPEE toughened and reinforced PET composite layer 2, and a second PET layer 3. The thickness of the first PET layer 1 and the second PET layer 3 are both 25-200 μm, the thickness of the TPEE toughened and reinforced PET composite layer 2 is 50-2000 μm, and the TPEE toughened and reinforced PET composite layer 2 is filled with a fiber skeleton, and the fiber skeleton is 0° fiber and / or 90° fiber and / or plain woven fiber mesh; The dimensions of the obtained composite prepreg tape are 1200 mm in length, 1000 mm in width, and a standard thickness of 0.1-2.4 mm; Step 2: First, a composite prepreg tape is hot-pressed on a PET foam substrate through a dedicated batch FPET Block production system, and then another PET foam substrate is hot-pressed on the composite prepreg tape, and the two PET foam substrates are hot-pressed and composited through the composite prepreg tape to form a double-stacked PET foam board; Step 3, the two stacked PET foam boards are laminated at least sequentially from bottom to bottom on the composite prepreg tape / PET foam substrate / …… / PET foam substrate / PET foam substrate / PET foam substrate to form n+1 stacked PET foam boards, i.e., semi-finished FPET Block; Step 4: heat-treating the semi-finished FPET Block, the heat-treatment parameters are as follows: heat-treating at 80-90° C. for 200-400 seconds, and naturally cooling to room temperature to obtain the finished standard FPET Block; Step five, groove the obtained PET foam composite core material substrate (the groove size needs to be positioned and grooved according to the design requirements of different types of PET foam composite core materials. Taking the classic PET foam composite core material as an example, the groove depth of the tic-tac-toe groove of the classic PET foam composite core material is 23mm, and the interval between grooves is 25mm), drill holes (the diameter of the resin pouring hole is 2mm, and the interval between adjacent resin pouring holes is 30mm), cut and level the edges, and grind to obtain the finished PET foam composite core material.
[0048] The TPEE toughened and reinforced PET composite layer 2 is prepared from TPEE toughened and reinforced PET masterbatch by extrusion melting, casting, stretching and cooling. The thickness of the TPEE toughened and reinforced PET composite film is 50-2000 μm.
[0049] In order to improve the bonding strength between the composite prepreg tape and the PET foam substrate, the inventors proposed two solutions: the first one is to perform low-temperature plasma treatment on the surface of the composite prepreg tape; the second one is to perform low-temperature plasma treatment on the surface of the PET foam substrate. The low-temperature plasma treatment parameters in the actual test are as follows: power 1000W, gas pressure 0.25MPa, working gas is nitrogen, and treatment time is 3min.
[0050] The fiber skeleton filled in the TPEE toughened and reinforced PET composite film has the function of toughening and reinforcing the TPEE toughened and reinforced PET composite film. When the fiber skeleton contains thermal conductive material, the fiber skeleton not only plays a role of toughening and reinforcing, but also improves the overall thermal conductivity of the composite prepreg tape.
[0051] The fiber skeleton is 0° fiber and / or 90° fiber and / or plain woven fiber mesh, which can be used in combination according to the mechanical property design requirements of the PET foam composite core material. The present invention provides the following combination schemes: Specific combination scheme ①: The fiber skeleton is 0° fiber. The laying method of 0° fiber can be multi-layer intermittent laying or single-layer laying, which is designed according to the actual thickness of the composite prepreg tape. The composite prepreg tape structure prepared by multi-layer intermittent laying of 0° fiber can be found in Figure 2 ② and ③, the composite prepreg tape structure prepared by laying a single layer of 0° fibers can be found in Figure 2 ① in the figure. The 0° fiber includes at least one of glass fiber, carbon fiber, basalt fiber, aramid fiber, and ultra-high molecular weight polyethylene fiber distributed along the X-axis direction. Common choices for 0° fiber are low-cost glass fiber and basalt fiber. As the composite prepreg has higher requirements for tensile strength, any one of aramid fiber, ultra-high molecular weight polyethylene fiber, and carbon fiber is selected in the 0° fiber in combination with any one of low-cost glass fiber and basalt fiber.
[0052] Specific combination scheme ②: The fiber skeleton is 90° fiber, and the laying method of 90° fiber can be multi-layer interval laying or single-layer laying. The laying method of 90° fiber is selected according to the actual thickness of the composite prepreg tape. The 90° fiber includes at least one of glass fiber, carbon fiber, basalt fiber, aramid fiber, and ultra-high molecular weight polyethylene fiber distributed along the Y-axis direction.
[0053] Specific combination scheme ③: The fiber skeleton is a plain woven fiber mesh cloth. The laying method of the plain woven fiber mesh cloth can be multi-layer intermittent laying or single-layer laying. The laying method of the plain woven fiber mesh cloth is selected according to the actual thickness of the composite prepreg tape. The warp threads in the plain woven fiber mesh cloth include at least one of glass fiber, carbon fiber, basalt fiber, aramid fiber, and ultra-high molecular weight polyethylene fiber, and the weft threads in the plain woven fiber mesh cloth include at least one of glass fiber, carbon fiber, basalt fiber, aramid fiber, and ultra-high molecular weight polyethylene fiber. The common warp and weft threads in the plain woven fiber mesh cloth are glass fibers. Since the composite prepreg tape has higher requirements for tensile strength, the warp threads in the plain woven fiber mesh cloth are selected from glass fiber, aramid fiber, ultra-high molecular weight polyethylene fiber, and carbon fiber, and the weft threads in the plain woven fiber mesh cloth are selected from glass fiber, aramid fiber, ultra-high molecular weight polyethylene fiber, and carbon fiber.
[0054] Specific combination scheme ④: The fiber skeleton is 0° fiber and 90° fiber, and the laying methods include but are not limited to 0° fiber / 90° fiber, 0° fiber / 90° fiber as repeated unit laying, 0° fiber / 90° fiber / 0° fiber, 90° fiber / 0° fiber / 90° fiber and other laying methods. The thickness of the composite prepreg tape is determined by the number of laying layers of 0° fiber and 90° fiber.
[0055] Specific combination scheme ⑤: The fiber skeleton is 0° fiber and plain woven fiber mesh, and the laying methods include but are not limited to 0° fiber / plain woven fiber mesh, 0° fiber / plain woven fiber mesh / 0° fiber, 0° fiber / plain woven fiber mesh as repeated unit laying, etc. The thickness of the composite prepreg tape is determined by the number of laying layers of 0° fiber and plain woven fiber mesh.
[0056] Specific combination scheme ⑥: The fiber skeleton is 90° fiber and plain woven fiber mesh, and the laying methods include but are not limited to 90° fiber / plain woven fiber mesh, 90° fiber / plain woven fiber mesh / 90° fiber, 90° fiber / plain woven fiber mesh as repeated unit laying, etc. The thickness of the composite prepreg tape is determined by the number of laying layers of 90° fiber and plain woven fiber mesh.
[0057] Specific combination scheme ⑦: the fiber skeleton is 0° fiber, plain fiber mesh and 90° fiber, and the laying methods include but are not limited to 0° fiber / plain fiber mesh / 90° fiber, 0° fiber / plain fiber mesh / 90° fiber as repeated unit laying, 0° fiber / 90° fiber / plain fiber mesh / 90° fiber / 0° fiber, 90° fiber / 0° fiber / plain fiber mesh / 0° fiber / 90° fiber, etc. The thickness of the composite prepreg tape is determined by the number of laying layers of 0° fiber, 90° fiber and plain fiber mesh.
[0058] The PET foam composite core material for fan blades has high requirements for anti-shear strength and compressive performance. The preferred laying method of the fiber skeleton is 0° fiber / plain woven fiber mesh / 0° fiber, that is, 0° fiber / plain woven fiber mesh / 0° fiber is distributed from top to bottom inside the TPEE toughened and reinforced PET composite film. The preferred scheme is as follows: The preferred laying method of the fiber skeleton is 0° fiber / 0° fiber / plain woven fiber mesh / 0° fiber / 0° fiber, that is, 0° fiber / 0° fiber / plain woven fiber mesh / 0° fiber / 0° fiber is distributed from top to bottom inside the TPEE toughened and reinforced PET composite film, giving the PET foam composite core material for fan blades higher shear strength and compressive performance, but the cost of the PET foam composite core material for fan blades will inevitably increase.
[0059] The structure of the TPEE toughened and reinforced PET composite film is as follows: TPEE toughened and reinforced PET unit film / 0° fiber / TPEE toughened and reinforced PET unit film / 0° fiber / TPEE toughened and reinforced PET unit film / plain woven fiber mesh / TPEE toughened and reinforced PET unit film / 0° fiber / TPEE toughened and reinforced PET unit film / 0° fiber TPEE toughened and reinforced PET unit film. The 0° fiber is glass fiber filament, the warp in the plain woven fiber mesh is glass fiber filament (Jushi's alkali-free glass fiber filament yarn) and aramid long fiber (50D Kevlar long fiber) arranged at intervals, and the warp arrangement is: glass fiber filament / aramid long fiber / ... / aramid long fiber / glass fiber filament; the weft in the plain woven fiber mesh includes alkali-free glass fiber filament (Jushi's alkali-free glass fiber filament yarn) and aramid long fiber (50D Kevlar long fiber) arranged at intervals, and the weft arrangement is: glass fiber filament / aramid long fiber / ... / aramid long fiber / glass fiber filament. The mesh specifications formed by the plain weave are 1mm*1mm, 2mm*2mm, 3mm*3mm, 5mm*5mm, 10mm*10mm, 15mm*15mm, 20mm*20mm, etc. The mesh specifications formed by the plain weave of the customized plain woven fiber mesh in the test are 1mm*1mm.
[0060] In order to improve the hot pressing composite efficiency of the composite prepreg, a thermally conductive filler is added to the composite prepreg, and the thermally conductive filler forms a three-dimensional network thermally conductive structure in the composite prepreg, thereby improving the thermal conductivity of the composite prepreg and thus improving the overall hot pressing composite efficiency. The thermal conductivity of the composite prepreg is preferably 0.5-3.0W / m·K. Excessive addition of thermally conductive fillers will make the composite prepreg hard and brittle.
[0061] The thermal conductive filler filled in the composite prepreg tape includes at least one of aluminum oxide, aluminum nitride, silicon nitride, titanium nitride, boron nitride, silicon carbide, titanium carbide, and zirconium carbide, and at least one of graphene and carbon nanotubes. In the experiment, the thermal conductive filler filled in the composite prepreg tape consists of aluminum oxide and carbon nanotubes.
[0062] From the structural design of the composite prepreg, the thermal conductivity of the composite prepreg is determined by the thermal conductivity of the first PET layer 1, the TPEE toughened and reinforced PET composite layer 2, and the second PET layer 3, that is, the thermal conductivity of the first PET film, the TPEE toughened and reinforced PET composite film, and the second PET film are similar, and the thermal conductivity of the three is controlled to be 0.5-3.0 W / m·K, preferably 0.7-1.0 W / m·K.
[0063] From the point of view of the amount of thermal conductive filler (considering the production cost of the composite prepreg), the thermal conductive filler is composed of ultrafine spherical alumina and carbon nanotubes in a mass ratio of 19:1, which can ensure the thermal conductivity of the composite prepreg while reducing the amount of thermal conductive filler, which is conducive to reducing the production cost of the composite prepreg. When the thermal conductive filler is used, KH570 (γ-methacryloxypropyltrimethoxysilane) is used for surface treatment to facilitate the uniform dispersion of the thermal conductive filler in the resin matrix, thereby improving the mechanical strength and thermal conductivity of the film material.
[0064] The amount of thermal conductive filler added is 20±2wt%, and the thermal conductivity of the composite prepreg is 0.8±0.1W / m·K, which ensures the flexibility of the composite prepreg while improving the thermal conductivity and hot pressing composite efficiency. In the test, the amount of thermal conductive filler added is 20wt%, and the thermal conductivity of the composite prepreg is 0.8±0.05W / m·K. When the composite prepreg contains thermally conductive fillers, the composite prepreg is marked as a thermally conductive composite prepreg. The first PET layer 1 and the second PET layer 3 are PET thermally conductive films customized by Guangdong Shengyi Technology Co., Ltd. The thermal conductivity of the PET thermally conductive film is 0.75-0.80W / m·K. The TPEE toughened and reinforced PET composite layer 2 is a thermally conductive TPEE toughened and reinforced PET composite film with a thermal conductivity of 0.75-0.80W / m·K. The thermally conductive TPEE toughened and reinforced PET composite film is made from a thermally conductive PEE toughened and reinforced PET masterbatch (the formula contains thermally conductive fillers).
[0065] TPEE toughened and reinforced PET masterbatch is made of the following raw materials in percentage by mass: 25-40% TPEE resin, 3-6% compatibilizer, 0.5-3% PET adhesion promoter, 0.8-2% antioxidant, 0.5-1.0% UV inhibitor, 0.5-1.0% lubricant, 0.5-1.0% release agent, 0-15% filler, and the balance is PET resin.
[0066] The PET adhesion promoter can be selected from at least one of Yuanya Y-1900-1PET treating agent, Guangdong Ona Polymer's F-1 PET adhesion promoter, Deqian ADK adhesion promoter, 9041 adhesion promoter, HYCM-7555 adhesion promoter, epoxy silane, amino silane, isocyanate silane, and methacryloxy silane.
[0067] The antioxidant may be an organic phosphite antioxidant or an organic phenol antioxidant.
[0068] The anti-ultraviolet agent is a benzotriazole ultraviolet absorber, an oxalic acid amide type light stabilizer, a triazine type light stabilizer, and a hindered amine light stabilizer.
[0069] The compatibilizer can be selected from at least one of W5D polyester compatibilizer, W5F polyester compatibilizer, W5A polyester compatibilizer and cyclic maleic anhydride grafted product of Coase.
[0070] In addition, the compatibilizer can also be a modified PET resin with polar groups introduced into the benzene ring in the PET molecular chain, such as a PET resin with -Cl introduced into the benzene ring in the molecular chain, or a sulfonated PET resin with -SO2OH or -SO2Na introduced into the benzene ring in the molecular chain.
[0071] The release agent can be selected from PETSPT100 released from LG Korea or PETFR543BK507 from DuPont USA. The release agent is preferably PETSPT100 released from LG Korea.
[0072] PET resin is bottle-grade polyester chips, such as Wankai WK801, Sanfangxiang CZ-318, Hainan Yisheng-YS-Y01, Pan Asia FY1004, Huarun CR-8863, etc. Hainan Yisheng-YS-Y01 was used in the specific test.
[0073] The melting temperature of TPEE resin is 195-220℃, the bending elastic modulus is ≥180MPa, the tensile strength at cut is ≥24MPa, and the Shore hardness is 45-55D. TPEE resin can be selected from commercially available TPEE resins (such as BM / BS3450, BM / BS3550, LN5355HR, HB2045D, HB2055D of Suzhou Libo Plastic Technology Co., Ltd., H605B of Zhonglan Chenguang, and Hytrel4275 of DuPont).
[0074] For those who have higher physical and chemical performance requirements for TPEE resin, they can also entrust manufacturers (such as Kaizhong Materials Technology Co., Ltd.) to customize TPEE resin. In the synthesis design of TPEE resin: the hard segment of TPEE resin has a number average molecular weight of 10 4 ~3*10 4 The polybutylene terephthalate PBT, the soft segment has a number average molecular weight of 3*10 4 ~7*10 4 Aliphatic polycarbonate or aliphatic polyether / polycarbonate.
[0075] The fillers in the TPEE toughened and reinforced PET masterbatch include thermal conductive fillers and / or reinforcing fillers.
[0076] When the TPEE toughened and reinforced PET masterbatch contains thermally conductive fillers, the composite prepreg produced using the TPEE toughened and reinforced PET masterbatch is a thermally conductive composite prepreg. The thermally conductive fillers give the TPEE toughened and reinforced PET masterbatch better thermal conductivity, and its thermal conductivity coefficient is 0.5-3.0W / m·K. The thermally conductive filler includes at least one of aluminum oxide, aluminum nitride, silicon nitride, titanium nitride, boron nitride, silicon carbide, titanium carbide, and zirconium carbide, and at least one of graphene and carbon nanotubes. From the perspective of the amount and cost of the thermally conductive filler, the thermally conductive filler is preferably composed of ultrafine spherical aluminum oxide and carbon nanotubes in a mass ratio of 19:1.
[0077] Reinforcing fillers play a role in toughening and strengthening the composite prepreg. Reinforcing fillers include at least one of calcium carbonate, barium sulfate, kaolin, montmorillonite, silica powder, titanium dioxide, mica powder, quartz powder, shell powder, chopped carbon fiber, chopped glass fiber, and inorganic whiskers. From the perspective of the dosage cost of the reinforcing filler, the reinforcing filler is composed of ultrafine calcium carbonate and chopped glass fiber in a mass ratio of (4-7): 1. The chopped glass fiber can enhance the compressive strength and shear strength of the reinforced core material. If you want to improve the compressive strength and shear strength of the composite prepreg, the reinforcing filler is composed of a compound of ultrafine calcium carbonate, chopped glass fiber, and zinc oxide whiskers.
[0078] When the TPEE toughened and reinforced PET composite film does not require high thermal conductivity, the filler in the TPEE toughened and reinforced PET masterbatch is a reinforcing filler, and the preferred range of the reinforcing filler content is 5wt%. In the specific test, the reinforcing filler is 2000 mesh ultrafine calcium carbonate, 3mm long chopped glass fiber (Taian Senyang Composite Materials Co., Ltd.) and zinc oxide whisker with a mass ratio of 16:3:1.
[0079] The non-thermal conductive TPEE toughened and reinforced PET masterbatch is made of the following raw materials in percentage by mass: 35% TPEE resin LN5355HR, 5% compatibilizer-W5F polyester compatibilizer, 1% PET adhesion promoter 9041, 0.8% antioxidant 1024, 0.2% antioxidant 168, 0.8% anti-ultraviolet agent-UV-531, 1% lubricant-zinc stearate, 0.5% release agent PETSPT100, 5% filler (2000 mesh ultrafine calcium carbonate, 3mm long chopped glass fiber (Taian Senyang Composite Materials Co., Ltd.) and zinc oxide whisker in a mass ratio of 16:3:1), and the balance is PET resin YS-Y01.
[0080] When the TPEE toughened and reinforced PET composite film has high thermal conductivity requirements, the fillers in the TPEE toughened and reinforced PET masterbatch include thermal conductive fillers and reinforcing fillers, the mass ratio of thermal conductive fillers to reinforcing fillers is 4:1, the preferred range of thermal conductive filler content is 8wt%, and the preferred range of reinforcing filler content is 2wt%. The reinforcing filler is 2000 mesh ultrafine calcium carbonate, 3mm long chopped glass fiber (Taian Senyang Composite Materials Co., Ltd.) and zinc oxide whisker in a mass ratio of 16:3:1. The thermal conductive fillers are ultrafine spherical alumina and carbon nanotubes, and the mass ratio of ultrafine spherical alumina and carbon nanotubes is 19:1.
[0081] The thermally conductive TPEE toughened and reinforced PET masterbatch is made of the following raw materials in percentage by mass: 40% TPEE resin LN5355HR, 4% compatibilizer-W5F polyester compatibilizer, 1.5% PET adhesion promoter 9041, 0.8% antioxidant 1024, 0.2% antioxidant 168, 0.8% anti-ultraviolet agent-UV-531, 1% lubricant-zinc stearate, 0.5% release agent PETSPT100, 8wt% thermal conductive filler (ultrafine spherical alumina and carbon nanotubes in a mass ratio of 19:1), 2% reinforcing filler (2000 mesh ultrafine calcium carbonate, 3mm long chopped glass fiber (Taian Senyang Composite Materials Co., Ltd.) and zinc oxide whisker in a mass ratio of 16:3:1), and the remainder is PET resin YS-Y01. The thermal conductivity of the PEE toughened and reinforced PET unit film prepared by using the above TPEE toughened and reinforced PET masterbatch is 0.8±0.05 W / m·K.
[0082] The preparation method of the composite prepreg tape is as follows: Step 1: Preparation of TPEE toughened and reinforced PET composite film: S1.1, accurately measured TPEE resin, compatibilizer, PET adhesion promoter, antioxidant, UV resistant agent, lubricant, release agent, filler, PET resin are uniformly mixed and placed in a screw extruder for melt extrusion, wire drawing, cooling, granulation, and drying to obtain TPEE toughened and reinforced PET masterbatch; S1.2, placing the TPEE toughened and reinforced PET masterbatch in a screw extruder for melt extrusion, casting, biaxial stretching, shaping, and cooling to obtain a TPEE toughened and reinforced PET composite unit film. The thickness of the obtained TPEE toughened and reinforced PET composite unit film can be adjusted by adjusting the biaxial stretching parameters (transverse stretching coefficient and longitudinal stretching coefficient). After biaxial stretching treatment, the thickness of the TPEE toughened and reinforced PET composite unit film is adjusted to 50 / 100 / 140 / 200 / 300μm; the thickness of the TPEE toughened and reinforced PET composite unit film is preferably 140μm.
[0083] S1.3, laying TPEE toughened and reinforced PET composite unit film / 0° fiber / TPEE toughened and reinforced PET composite unit film / plain woven fiber mesh / TPEE toughened and reinforced PET composite unit film / 0° fiber / TPEE toughened and reinforced PET composite unit film from bottom to top on the bottom of the mold groove of the forming mold to obtain a semi-finished TPEE toughened and reinforced PET composite film, using a hot press to perform hot pressing and compounding treatment on the semi-finished TPEE toughened and reinforced PET composite film, the hot pressing plate of the hot press is embedded in the mold groove of the forming mold, and the semi-finished TPEE toughened and reinforced PET composite film is hot pressed and compounded, the surface temperature of the hot pressing plate is 225°C, the hot pressing pressure is 80N, the hot pressing duration is 200s, and it is cooled to room temperature to obtain a TPEE toughened and reinforced PET composite layer; Step 2: Cover the first PET film on one surface of the TPEE toughened and reinforced PET composite layer, and then cover the second PET film on the other surface of the TPEE toughened and reinforced PET composite layer to obtain a semi-finished composite film. The thickness of the first PET film and the second PET film can be selected as 50 / 80 / 100 / 120 / 200 μm. Preferably, the thickness of the first PET film is 80 μm, the thickness of the second PET film is 80 μm, and the thickness of the TPEE toughened and reinforced PET composite unit film is 80 μm. The semi-finished composite film is embedded in the mold groove of the molding mold, and the hot pressing plate of the hot press is embedded in the mold groove for hot pressing composite treatment. The surface temperature of the hot pressing plate is 245°C, the pressure applied by the hot pressing plate is 120N, and the hot pressing duration is 120s. Cool to room temperature, take out, and cut the edges to obtain a composite prepreg tape.
[0084] refer to Figure 3In order to adapt to the continuous production operation requirements of the dedicated batch FPET Block production system, the bonding strength between the composite prepreg tape 10 and the first release paper 8 in the composite prepreg tape roll is less than the bonding strength between the second release paper 9 and the composite prepreg tape 10.
[0085] Customization requirements for the first release paper 8: A non-silicone oil covered area is formed on the surface of the first release paper 8 in contact with the composite prepreg tape 10, and the bonding strength between the non-silicone oil covered area of the first release paper 8 and the composite prepreg tape 10 is greater than the bonding strength between the silicone oil covered area of the first release paper 8 and the composite prepreg tape 10.
[0086] Customization requirements for the second release paper 9: A non-silicone oil covered area is also formed on the surface of the second release paper 9 in contact with the composite prepreg tape 10, and the bonding strength between the non-silicone oil covered area of the second release paper 9 and the composite prepreg tape 10 is greater than the bonding strength between the silicone oil covered area of the second release paper 9 and the composite prepreg tape 10.
[0087] The non-silicone oil coverage area of the first release paper 8 is smaller than the non-silicone oil coverage area of the second release paper 9. Preferably, the non-silicone oil coverage area of the second release paper 9 is twice the non-silicone oil coverage area of the first release paper 8, so that the bonding strength between the composite prepreg tape 10 and the first release paper 8 is smaller than the bonding strength between the second release paper 9 and the composite prepreg tape 10, that is, the first release paper 8 is easier to be peeled off than the second release paper 9.
[0088] The purpose of designing the structure of the composite prepreg tape coil is to facilitate the peeling of the first release paper 8 after hot pressing the composite prepreg tape coil during the operation of the dedicated batch FPET Block production system. During the peeling process of the first release paper 8, the bonding strength between the second release paper 9 and the composite prepreg tape 10 is relatively large. The first release paper 8 is peeled off, while the second release paper 9 is not peeled off, thereby ensuring the overall batch and continuous production efficiency.
[0089] The spacing between adjacent composite prepreg tapes in the composite prepreg tape coil is equal to the spacing between two PET foam substrates transported on the conveyor belt assembly in the PET foam substrate hot pressing subsystem in the dedicated batch FPET Block production system. The transmission speed of the PET foam substrate is equal to the transmission speed of the composite prepreg tape coil. The synchronous transmission of the two can ensure the batch and continuous production of the standard FPET Block. In the specific design of the PET foam substrate hot pressing subsystem, the spacing between the two PET foam substrates is 2.4m, and the spacing between adjacent composite prepreg tapes on the composite prepreg tape coil is also 2.4m.
[0090] For example: the PET foam substrate on the conveyor belt of the conveyor belt assembly in the PET foam substrate hot pressing subsystem moves 2.4m, and the composite prepreg tape coil is also transported 2.4m. The speed of the PET foam substrate transported on the conveyor belt is equal to the transmission speed of the composite prepreg tape coil. The PET foam substrate and the composite prepreg tape are hot pressed and composited on the second hot pressing roller. After the hot pressing is completed, the next new PET foam substrate is transported from the starting end of the conveyor belt. The spacing between the two PET foam substrates is 2.4m, and the adjacent composite prepreg tapes on the composite prepreg tape coil are 2.4m. The synchronous transmission of the two can ensure the overall batch and continuous production.
[0091] refer to Figure 4 In order to mass produce composite prepreg coils, the inventors designed a production device for composite prepreg coils. The structure of the production device for composite prepreg coils is as follows, including a second release paper receiving roller 7, a first guide roller 71, a first flattening roller group 72, a composite prepreg hot pressing assembly 73, a second flattening roller group 74, a first release paper receiving roller 75, a second guide roller 76, a first hot pressing roller 77, a second hot pressing roller 78, and a composite prepreg coil receiving roller 79.
[0092] refer to Figure 4 The composite prepreg tape hot pressing assembly 73 includes a first hot pressing plate 731 fixedly connected to the ground by a bracket, and a second hot pressing plate 732 fixedly connected to the cylinder, and the cylinder is fixedly connected to the gantry. The second hot pressing plate 732 can move up and down under the drive of the cylinder, that is, the second hot pressing plate 732 moves toward the first hot pressing plate 731 under the drive of the cylinder to hot press the composite prepreg tape on the first hot pressing plate 731. The first hot pressing plate 731 is a hot steel plate, and the surface temperature of the hot steel plate is 120-140°C. In specific production, the first hot pressing plate 731 is a hot steel plate, and the surface temperature of the hot steel plate is 130±0.5°C. The second hot pressing plate 732 is a steel plate coated with polytetrafluoroethylene, and the surface temperature is room temperature.
[0093] refer to Figure 4 , the relative ground height of the first guide roller 71 is lower than the first flattening roller group 72, and the relative ground height of the second release paper receiving roller 7 is higher than the first flattening roller group 72. The relative ground heights of the first release paper receiving roller 75 and the second guide roller 76 are higher than the second flattening roller group 74. And the relative ground height of the first release paper receiving roller 75 is higher than the relative ground height of the second guide roller 76. The first flattening roller group 72 includes a plurality of first flattening rollers, and the upper roller surfaces of the first flattening rollers are all in the same horizontal plane, and the upper roller surfaces of the first flattening rollers are also in the same horizontal plane as the surface of the first hot pressing plate 731.
[0094] refer to Figure 4The second flattening roller group 74 includes a second flattening roller, and the upper roller surfaces of the second flattening rollers are all in the same horizontal plane. The upper roller surface of the second flattening roller is also in the same horizontal plane as the surface of the first hot pressing plate 731. The first release paper receiving roller 75 and the second guide roller 76 are located above the second flattening roller group 74. The upper roller surface of the first hot pressing roller 77 is also in the same horizontal plane as the surface of the first hot pressing plate 731. The central axes of the first hot pressing roller 77 and the second hot pressing roller 78 are in the same vertical plane. The first hot pressing roller 77 is a steel roller, and the roller surface temperature is room temperature. The second hot pressing roller 78 is a fluororubber roller, and the roller surface temperature is 120-140°C. In the actual prototype, the roller surface temperature of the second hot pressing roller 78, i.e., the fluororubber roller, is 130±0.5°C.
[0095] refer to Figure 4 The gap between the first hot pressing roller 77 and the second hot pressing roller 78 is equal to 0.995-1.00 times the total thickness of the first release paper, the composite prepreg tape and the second release paper. The gap between the first hot pressing roller 77 and the second hot pressing roller 78 can be adjusted by adjusting the height of the second hot pressing roller 78 to adapt to the production of composite prepreg tape coils of different thicknesses.
[0096] In the actual prototype, the gap between the first hot-pressing roller 77 and the second hot-pressing roller 78 is equal to one times the total thickness of the first release paper 8 , the composite prepreg tape 10 , and the second release paper 9 .
[0097] refer to Figure 3 The working method of the production equipment for composite prepreg tape coils is as follows: the second release paper 9 on the second release paper storage roll 7 is transported to the first flattening roller group 72 through the first guide roller 71 for flattening, the flattened second release paper 9 is input between the first hot pressing plate 731 and the second hot pressing plate 732 of the composite prepreg tape hot pressing assembly 73, the machine is stopped so that the second release paper 9 is stagnant in the composite prepreg tape hot pressing assembly 73, the composite prepreg tape 10 is manually placed on the upper surface of the flattened second release paper 9, the cylinder of the composite prepreg tape hot pressing assembly 73 is turned on so that the second hot pressing plate 732 is driven by the cylinder to move toward the first hot pressing plate The plate 731 moves to hot-press the composite prepreg 10 on the first hot pressing plate 731, so that the composite prepreg 10 is compounded on the upper surface of the second release paper 9 to obtain a semi-finished product. The machine is turned on, and the semi-finished product passes through the second flattening roller group 74 and the first hot pressing roller 77 during transmission. At the same time, the first release paper 8 on the first release paper receiving roller 75 passes through the second guide roller 76 and is input between the first hot pressing roller 77 and the second hot pressing roller 78. Under the hot pressure of the first hot pressing roller 77 and the second hot pressing roller 78, the first ion type 8 is compounded on the upper surface of the semi-finished product, and the obtained finished composite prepreg coil is rolled up and stored on the composite prepreg coil receiving roller 79.
[0098] The dedicated batch FPETBlock production system used in the preparation method of the PET foam composite core material for wind turbine blades of the present invention is adapted to the continuous production of standard FPET Block.
[0099] refer to Figure 5-6 The dedicated batch FPET Block production system includes a plurality of PET foam substrate hot pressing subsystems 4 and an FPET Block heat treatment subsystem 40. The PET foam substrate hot pressing subsystem 4 is used to hot press and compound the PET foam substrate / composite prepreg tape / PET foam substrate to form a two-layer PET foam board or to hot press and compound n-layer PET foam boards / composite prepreg tape / PET foam substrate to form n+1-layer PET foam boards. The batch and continuous production of the semi-finished FPET Block is realized through the plurality of PET foam substrate hot pressing subsystems 4. The semi-finished FPET Block is heat treated by the FPET Block heat treatment subsystem 40 to obtain a finished standard FPET Block.
[0100] The number of PET foam substrate hot pressing and bonding subsystems 4 determines the number of PET foam substrates hot pressed and bonded in the finished standard FPET Block. The number of PET foam substrates hot pressed and bonded in the finished standard FPET Block determines the length of the finished PET foam composite core material. Non-standard FPET Block production can also be carried out by using a dedicated batch FPET Block production system.
[0101] For example: Taking a typical FPET Block as an example, the dimensions of the PET foam substrate in the FPET Block are 1200mm long, 1000mm wide and 50mm high, while the dimensions of the standard FPET Block are 1200mm long, 1000mm wide and 1000mm high. In the actual production process, 20 PET foam substrates + 19 composite prepreg tapes are hot-pressed and compounded to form the finished standard FPET Block.
[0102] The number of PET foam substrate hot pressing and sealing subsystems 4 in the dedicated batch FPET Block production system depends on the arrangement of the PET foam substrate hot pressing and sealing subsystems 4. The required number of PET foam substrate hot pressing and sealing subsystems 4 is 19, and adjacent PET foam substrate hot pressing and sealing subsystems 4 are connected end to end.
[0103] Alternatively, 9 PET foam substrate hot pressing and joining subsystems 4 are used to form a semi-finished FPET Block production line. The semi-finished FPET Block produced is a ten-ply PET foam board (made by hot pressing 10 PET foam substrates + hot pressing 9 composite prepreg tapes). The 9 PET foam substrate hot pressing and joining subsystems 4 are connected end to end. Another PET foam substrate hot pressing and joining subsystem 4 is installed to hot press two semi-finished FPET Blocks with composite prepreg tapes to form a FPET Block reference block (made by hot pressing 20 PET foam substrates + hot pressing 19 composite prepreg tapes). The FPET Block reference block is input into the FPET Block heat treatment subsystem 40 for heat treatment. After the heat treatment is completed, the finished standard FPET Block is obtained. The number of PET foam substrate hot pressing and joining subsystems 4 required in the dedicated batch FPETBlock production system is 9+1. This layout can reduce the number of PET foam substrate hot pressing and joining subsystems 4 and reduce equipment costs.
[0104] Alternatively, four PET foam substrate hot pressing and joining subsystems 4 are used, and the four PET foam substrate hot pressing and joining subsystems 4 are connected end to end to produce five-stack PET foam boards (made by hot pressing 5 PET foam substrates + hot pressing and joining 4 composite prepreg tapes), and two more PET foam substrate hot pressing and joining subsystems 4 are arranged, wherein one PET foam substrate hot pressing and joining subsystem 4 hot presses and joins two five-stack PET foam boards to form ten-stack PET foam boards (made by hot pressing 10 PET foam substrates + hot pressing and joining 9 composite prepreg tapes), and the other PET foam substrate hot pressing and joining subsystem 4 hot presses and joins two ten-stack PET foam boards (made by hot pressing 10 PET foam substrates + hot pressing and joining 9 composite prepreg tapes) to form a semi-finished product FPET Block (made by hot pressing 20 PET foam substrates + hot pressing and joining 19 composite prepreg tapes), and the semi-finished product FPETBlock output by the PET foam substrate hot pressing and joining subsystem 4 is input into the FPET The block heat treatment subsystem 40 performs heat treatment, and the finished standard FPETBlock is obtained after the heat treatment. Then the number of PET foam substrate heat pressing subsystems 4 required in the dedicated batch FPET Block production system is 4+1+1. This layout can reduce the number of PET foam substrate heat pressing subsystems 4 and reduce equipment costs.
[0105] In order to ensure the production efficiency of the finished standard FPET Block, it is preferred that the number of PET foam substrate hot pressing subsystems 4 is 19, and adjacent PET foam substrate hot pressing subsystems 4 are connected end to end. When preparing the actual test sample, one PET foam substrate hot pressing subsystem 4 is used to produce the semi-finished FPET Block (20 PET foam substrates hot pressing + 19 composite prepreg tapes hot pressing composite).
[0106] In order to help readers fully understand the continuous preparation method of PET foam composite core materials for wind turbine blades, the specific structure of the dedicated batch FPET Block production system is described in detail, see the following content.
[0107] refer to Figure 6-7 The single PET foam substrate hot pressing subsystem 4 includes a conveying belt assembly 41, a composite prepreg coil storage roller 42, a first release paper peeling roller 43, a first hot pressing roller 44, a first release paper recovery roller 45, a laser scanning and heating assembly 46, a second hot pressing roller 47, a second release paper recovery roller 48, a third hot pressing roller 49, a leveling roller 5, and a PET foam substrate handling assembly 6.
[0108] refer to Figure 6-7 The composite prepreg coil is stored in the composite prepreg coil storage roller 42 of the PET foam substrate hot pressing subsystem 40 on the dedicated batch FPET Block production system. The composite prepreg coil storage roller 42 is used to roll up the composite prepreg coil produced by the composite prepreg coil production equipment. The conveyor belt surface on the conveyor belt assembly 41 is integrally formed with a plurality of rubber protrusions to form a PET foam substrate limiting frame. The spacing between adjacent PET foam substrate limiting frames is equal to the adjacent composite prepreg tapes on the composite prepreg coil, that is, the spacing between adjacent PET foam substrates is equal to the adjacent composite prepreg tapes on the composite prepreg coil. The transmission speed of the PET foam substrate is equal to the transmission speed of the composite prepreg coil, which is convenient for manually placing the PET foam substrate accurately into the PET foam substrate limiting frame or using the PET foam substrate handling assembly 6 to accurately place the PET foam substrate into the PET foam substrate limiting frame to ensure the overall continuous production.
[0109] refer to Figure 6-7, the central axis of the composite prepreg coiled material receiving roller 42 and the first release paper recycling roller 45 are located in the same plane and perpendicular to the horizontal plane, and the composite prepreg coiled material receiving roller 42 is located above the first release paper recycling roller 45. The central axis of the first hot pressing roller 44 and the first release paper peeling roller 43 are located in the same plane and perpendicular to the horizontal plane, and the first hot pressing roller 44 is located directly above the first release paper peeling roller 43. The spacing between the first hot pressing roller 44 and the first release paper peeling roller 43 is equal to 0.98-1.00 times the thickness of the composite prepreg coiled material. In the actual prototype design, the spacing between the first hot pressing roller 44 and the first release paper peeling roller 43 is equal to 1.00 times the thickness of the composite prepreg coiled material.
[0110] The first hot pressing roller 44 is a hot steel roller with a roller surface temperature of 80-98° C. In the actual prototype design, the roller surface temperature of the first hot pressing roller is 85° C. The first release paper peeling roller 43 is a hot steel roller with a roller surface temperature of 120-140° C. In the actual prototype design, the roller surface temperature of the first release paper peeling roller 43 is 125° C.
[0111] The speed of the conveyor belt assembly 41 in conveying the PET foam substrate is equal to the speed of the composite prepreg coil, and the speed of the composite prepreg coil is 3.0-8.0 cm / s. In the actual prototype design, the speed of the composite prepreg coil is 5.0 cm / s. The spacing between adjacent PET foam substrates is 2.4 m, and the transmission time of the PET foam substrate and the transmission time of the composite prepreg coil are 48 s.
[0112] refer to Figure 7-8 The laser scanning and heating assembly 46 is disposed between the first release paper peeling roller 43 and the second hot pressing roller 47. The laser scanning and heating assembly 46 includes a first screw 461 that is rotatably and fixedly connected to a bracket, a screw drive motor 462 that is fixedly connected to the bracket and is used to drive the first screw 461 to rotate around its own axis, and a laser emitter A463 that moves along the axial direction of the first screw 461. The line-surface angle formed by the laser emitted by the laser emitter A463 and the composite prepreg tape is 45-135°. In the actual prototype design, the line-surface angle formed by the laser emitted by the laser emitter A463 and the composite prepreg tape is 90°.
[0113] The scanning speed of the laser emitter A463 is 0.2-2.0m / s, the laser scanning power is 200-500W, and the surface temperature of the composite prepreg tape after laser scanning is 180-240°C. In the actual prototype design, the scanning speed of the laser emitter A463 is 1.0±0.05m / s, and the scanning speed of the laser emitter A463 is set to 1m / s. The preferred range of the laser scanning power is 300-400W, and the laser scanning power of the laser emitter A463 is set to 360W.
[0114] Based on the scanning speed of the laser emitter A463 being 1 m / s and the laser scanning power being 360 W, the surface temperature of the composite prepreg tape after laser scanning is 210.0±0.50°C.
[0115] refer to Figure 6-7 , the second hot-pressing roller 47 is located downstream of the first release paper peeling roller 43 and the vertical distance between the second hot-pressing roller 47 and the horizontal plane of the conveyor belt of the conveyor belt assembly 41 is equal to 0.98-1.00 times the total thickness of the PET foam substrate and the composite prepreg tape. Preferably, the vertical distance between the second hot-pressing roller 47 and the horizontal plane of the conveyor belt of the conveyor belt assembly 41 is equal to 0.995-1.00 times the total thickness of the PET foam substrate and the composite prepreg tape. In the actual prototype design, the vertical distance between the second hot-pressing roller 47 and the horizontal plane of the conveyor belt of the conveyor belt assembly 41 is equal to 1.0 times the total thickness of the PET foam substrate and the composite prepreg tape.
[0116] The second hot pressing roller 47 is connected to the driving motor, the speed of the second hot pressing roller 47 is 3-8 cm / s, and the transmission speed of the composite prepreg coil is 3-8 cm / s. In the specific preparation, the speed of the second hot pressing roller 47 is set to 5 cm / s.
[0117] The second hot pressing roller 47 is a fluororubber roller, and the roller surface temperature is 105-120° C. Specifically, in the preparation of the PET foam composite core material, the roller surface temperature of the second hot pressing roller 47, i.e., the fluororubber roller, is 120° C.
[0118] refer to Figure 6-7 , the central axis of the second hot pressing roller 47 and the second release paper recovery roller 48 are located in the same plane perpendicular to the horizontal plane, that is, the second release paper recovery roller 48 is located directly above the second hot pressing roller 47, and the peeled release paper can be recycled. The third hot pressing roller 49 is located downstream of the second hot pressing roller 47. The vertical distance between the third hot pressing roller 49 and the horizontal plane of the conveyor belt of the conveyor belt assembly 41 is equal to 0.99-1.00 times the total thickness of the PET foam substrate and the composite prepreg tape. Preferably, the vertical distance between the third hot pressing roller 49 and the horizontal plane of the conveyor belt of the conveyor belt assembly 41 is equal to 0.998-1.00 times the total thickness of the PET foam substrate and the composite prepreg tape. In the actual prototype design, the vertical distance between the third hot pressing roller 49 and the horizontal plane of the conveyor belt of the conveyor belt assembly 41 is equal to 1.00 times the total thickness of the PET foam substrate and the composite prepreg tape.
[0119] The third hot pressing roller 49 is a polytetrafluoroethylene composite roller, which includes a heat-conducting polytetrafluoroethylene outer layer and a steel inner roller. The heat-conducting polytetrafluoroethylene outer layer has an introduction coefficient of 0.5-2.0 W / m·K. The measured surface thermal conductivity of the polytetrafluoroethylene composite roller is 1.04 W / m·K.
[0120] The roller surface temperature of the polytetrafluoroethylene composite roller is 145-180° C. Specifically, the roller surface temperature of the third hot pressing roller 49, i.e., the polytetrafluoroethylene composite roller, for preparing the PET foam composite core material is 165° C.±0.5° C.
[0121] refer to Figure 6-7 The PET foam substrate conveying assembly 6 is arranged between the third hot pressing roller 49 and the leveling roller 5, and is used to convey a new PET foam substrate, and hot-press and compound the conveyed PET foam substrate with the PET foam substrate with the composite prepreg tape to form 2 stacks of PET foam boards; or hot-press and compound the conveyed PET foam substrate with the PET foam substrate with the composite prepreg tape or n stacks of PET foam boards with the composite prepreg tape to form n+1 stacks of PET foam boards, thereby obtaining a FPET Block with a thickness of 50*(n+1) mm.
[0122] refer to Fig.10 The PET foam substrate handling assembly 6 includes a support base 61, a crossbar assembly 62 that moves up and down along the support base 61, and a clamping claw assembly 63 that moves left and right along the crossbar assembly 62. The support base 61 is provided with a sliding groove for the crossbar assembly 62 to move up and down along its length direction. The crossbar assembly 62 is fixedly connected to an electric push cylinder A620, which is fixedly connected to the support base 61. The push rod of the electric push cylinder A620 is fixedly connected to the crossbar assembly 62. The electric push cylinder A620 controls the crossbar assembly 62 to move up and down in the sliding groove of the support base 61 to adjust the clamping height of the clamping claw assembly 63. The clamping claw assembly 63 moves left and right on the crossbar assembly 62 to clamp the PET foam substrate and carry it to a designated position of the conveyor belt of the conveyor belt assembly 41.
[0123] refer to Fig.10 The crossbar assembly 62 includes two supporting slide bars 621, and a sliding screw rod 622 fixedly and rotatably connected to the two supporting slide bars 621. One end of the sliding screw rod 622 is rotatably passed through a supporting slide bar 621 and is located outside the bottom surface of the supporting slide bar 621. The sliding screw rod 622 located outside the bottom surface of the supporting slide bar 621 is fixedly connected to a stepper motor 623 through a coupling. The stepper motor 623 drives the sliding screw rod 622 to rotate around its own axis, so that the clamping jaw assembly 63 moves left and right on the sliding screw rod 622.
[0124] refer to Figure 10-11The clamping jaw assembly 63 includes a connecting piece 631 threadedly connected to the sliding screw 622, a main pipe A632 is fixedly connected to the lower surface of the connecting piece 631, a sliding pipe A633 is slidably connected inside the main pipe A632, a limiting ring 6331 is fixedly connected to the outer wall of the sliding pipe A633, and the sliding pipe A633 slides up and down inside the main pipe A632. Two axially symmetrical first cylinders 634 are fixedly connected to the outer wall of the main pipe A632. The push rod of the first cylinder 632 is fixedly connected to the peripheral side of the limiting ring 6331, that is, the first cylinder 632 can drive the sliding pipe A633 to slide up and down inside the main pipe A632. A platform plate 635 is fixedly connected to the bottom surface of the sliding pipe A633. Two axially symmetrical second cylinders 636 are fixedly connected to the upper surface of the platform plate 635. The push rod of the second cylinder 636 is penetrated and slidably connected to the platform plate 635, and the push rod of the second cylinder 636 is fixedly connected to the suction plate 637.
[0125] refer to Figure 10-11 The center of the upper surface of the suction disk 637 is fixedly connected with a laser emitter B6371. The emitting end of the laser emitter B6371 passes through the suction disk 637 and is located outside the center of the lower surface of the suction disk 637. The emitting end of the laser emitter B6371 is exposed to the suction disk 637 by 1mm, that is, the center of the PET foam substrate is positioned by laser, which improves the accuracy of clamping and improves the overall production efficiency. A rubber pad 6372 with a thickness of 1.2-1.5mm is fixedly connected to the bottom surface of the suction disk 637, and a nano-glue layer is fixedly connected to the bottom surface of the rubber pad 6372. A plurality of clamping claw arms 638 are detachably and fixedly connected to the peripheral side of the platform disk 635.
[0126] refer to Figure 10-11 The clamping claw arm 638 includes a main pipe B6381, in which a sliding pipe B6382 is slidably connected. The outer wall of the sliding pipe B6382 is fixedly connected to a limiting ring plate 6383. The outer wall of the main pipe B6381 is fixedly connected to a third cylinder 6384. The push rod of the third cylinder 6384 is fixedly connected to the peripheral side of the limiting ring plate 6383, that is, the third cylinder 6384 can drive the sliding pipe B6382 to slide up and down in the main pipe B6381. One end of the clamping claw arm 638 is detachable and fixedly connected to the peripheral side of the platform plate 635, and the other end is detachable and fixedly connected to a clamp 639, that is, the bottom of the sliding pipe B6382 is detachable and fixedly connected to the clamp 639.
[0127] refer to Figure 10-11The clamp 639 includes a rectangular support block 6391, a fourth cylinder 6392, and a positioning cone 6393. The rectangular support block 6391 is detachable and fixedly connected to the bottom of the sliding tube B6382, and the rectangular support block 6391 is perpendicular to the horizontal plane. The fourth cylinder 6392 is fixedly connected to the outer side of the rectangular support block 6391. The push rod of the fourth cylinder 6392 slides through the rectangular support block 6391 and is located on the inner side of the inner side of the rectangular support block 6391. The positioning cone 6393 is fixedly connected to the push rod surface of the fourth cylinder 6392 that slides through the rectangular support block 6391. The fourth cylinder 6392 pushes the positioning cone 6393 to move in the horizontal direction to clamp the PET foam substrate.
[0128] refer to Figure 10-11 The third cylinder 6384 can drive the sliding tube B6382 to slide up and down in the main tube B6381 to adjust the position of the positioning cone 6393, so that the clamping point of the positioning cone 6393 can be positioned at the side center of the PET foam substrate, thereby improving the overall clamping and carrying stability of the clamping claw arm 638.
[0129] refer to Figure 10-11 , the specific connection method between the clamping claw arm 638 and the platform plate 635 is as follows: the outer wall of the platform plate 635 is fixedly connected to two circular disk bodies A, and the two circular disk bodies A are coaxially spaced. One end of the main tube B6381 of the clamping claw arm 638 is fixedly connected to the circular disk body B, and the circular disk body B is coaxially arranged between the two circular disk bodies A. The two circular disk bodies A and the circular disk body B are penetrated with fixing screws. After adjusting the inclination angle of the clamping claw arm 638, the fixing screw is screwed with the nut, and the clamping claw arm 638 can be fixedly connected to the platform plate 635. In order to adapt to the length of the PET foam substrate, the inclination angle of the clamping claw arm 638 and the outward sliding distance of the sliding tube B6382 can be adjusted to meet the processing and production of non-standard PET foam substrates.
[0130] refer to Figure 10-11 , the specific connection method between the clamp 639 and the sliding tube B6382 on the clamping claw arm 638 is as follows: the other end of the main tube B6381 of the clamping claw arm 638 is fixedly connected to two circular disc bodies C, and the two circular disc bodies C are coaxially arranged at intervals. The upper surface of the rectangular parallelepiped bearing block 6391 is fixedly connected to a circular disc body D, and the circular disc body D is coaxially arranged between the two circular disc bodies C. The two circular disc bodies C and the circular disc body D are penetrated with fixing screws. The rectangular parallelepiped bearing block 6391 is adjusted to be perpendicular to the horizontal plane, and the fixing screw is screwed with a nut, so that the clamp 639 can be detachably and fixedly connected to the clamping claw arm 638.
[0131] refer to Figure 6-7The height difference between the vertical distance between the leveling roller 5 and the horizontal plane of the conveyor belt assembly 41 and the vertical distance between the second hot pressing roller 47 and the horizontal plane of the conveyor belt assembly 41 is the height of a single PET foam substrate. The n+1 stacks of PET foam boards leveled by the leveling roller 5 are input into the next PET foam substrate hot pressing subsystem 4.
[0132] When the PET foam substrate hot pressing and sealing subsystem 4 is used as the starting end PET foam substrate hot pressing and sealing subsystem, a limited position frame area is set at the starting end of the conveyor belt on the conveyor belt assembly 41. The limited position frame area at the starting end of the conveyor belt needs to load the PET foam substrate. The first PET foam substrate loading method is to carry the PET foam substrate carrying assembly 6, and the second foam substrate loading method is to manually carry the PET foam substrate.
[0133] The PET foam substrate hot pressing and sealing subsystem 4 except for the PET foam substrate hot pressing and sealing subsystem as the starting end, the starting end of the conveyor belt on the conveyor belt assembly 41 is divided into an n+1 stack of PET foam boards quality inspection area, and the operator will perform an appearance inspection on the n+1 stack of PET foam boards to determine the quality of the n+1 stack of PET foam boards.
[0134] refer to Figure 6-7 , the working mode of PET foam substrate hot pressing subsystem 4: Step A: The composite prepreg coil unwound by the composite prepreg coil receiving roller 42 passes through the first release paper peeling roller 43, and the first release paper is peeled off. The surface angle of the composite prepreg stripped of the first release paper and the laser emitted from the laser emitter 463 is 90°. The composite prepreg with the second release paper preheated by the laser scanning heating component 46 is transferred to the first hot pressing roller 44. The second release paper is attached to the roller surface of the second hot pressing roller 47. The composite prepreg stripped of the first release paper is transferred to the conveyor belt component 41. The upper surface of the PET foam substrate or the n-stack PET foam boards is hot-pressed and laminated, the transmission speed of the composite prepreg tape is equal to the transmission speed of the PET foam substrate or the n-stack PET foam boards, and the bonding force between the composite prepreg tape and the upper surface of the PET foam substrate or the n-stack PET foam boards is greater than the bonding force between the composite prepreg tape and the second release paper, the composite prepreg tape and the PET foam substrate or the n-stack PET foam boards are hot-pressed and laminated, and the second release paper is separated on the second hot pressing roller 47, and the peeled second release paper is rolled up and recovered on the second release paper recovery roller 48.
[0135] Process B: After hot pressing by the second hot pressing roller 47, the composite prepreg is hot-pressed and composited with the PET foam substrate or the upper surface of the n-stack PET foam boards. The PET foam substrate of the upper surface hot-pressed composite prepreg output by the second hot pressing roller 47 or the n-stack PET foam boards of the upper surface hot-pressed composite prepreg are input into the third hot pressing roller 49. The third hot pressing roller 49 performs hot pressing and melting treatment on the upper surface of the composite prepreg.
[0136] Step C: After the hot pressing and melting treatment by the third hot pressing roller 49, the PET foam substrate is then fed into the working area of the PET foam substrate conveying assembly 6, the conveyor belt assembly 41 stops (the composite prepreg tape coil also stops conveying), and the PET foam substrate conveying assembly 6 clamps and carries another PET foam substrate just above the PET foam substrate or the n-stack PET foam board, and hot presses the other PET foam substrate on the upper surface of the hot pressed composite prepreg PET foam substrate to form two stacks of PET foam boards, or hot presses the other PET foam substrate on the upper surface of the hot pressed composite prepreg n-stack PET foam board to form n +1 stack of PET foam boards, and then the conveyor belt assembly 41 is started (the composite prepreg coil also starts to be transported), and the obtained 2 stacks of PET foam boards or the obtained n+1 stacks of PET foam boards are input into the leveling roller 5 for hot pressing and leveling treatment, and the 2 stacks of PET foam boards or the obtained n+1 stacks of PET foam boards obtained after the leveling treatment are input into the next PET foam substrate hot pressing and bonding subsystem 4 for hot pressing and bonding new PET foam substrates, so as to obtain 3 stacks of PET foam boards or the obtained n+2 stacks of PET foam boards, and thus, after passing through several PET foam substrate hot pressing and bonding subsystems 4, semi-finished product FPET Block (20 stacks of PET foam boards) can be mass-produced, and the semi-finished product FPET Block is further heat-treated by the FPET Block heat treatment subsystem 40, heat-treated at 80-90°C for 200-400s, and naturally cooled to room temperature to obtain a finished standard FPET Block.
[0137] refer to Fig. 9 The FPET Block heat treatment subsystem 40 includes a conveyor belt assembly 401, an oven 402, and a hot pressing roller group 403. The oven 402 is fixedly connected to the conveyor belt assembly 401. The temperature in the oven 402 is 80-90°C. Preferably, the temperature in the oven 402 is set to 88°C. The length of the oven 402 is controlled to be 4-6m, and the transmission speed of the semi-finished FPET Block is 1-10cm / s. Preferably, the length of the oven 402 is controlled to be 5m, and the transmission speed of the semi-finished FPET Block is 2±0.2cm / s. The specific transmission speed is set to 2cm / s, that is, the heat treatment parameters in step five are heat treatment at 88°C for 250s.
[0138] refer to Fig. 9The hot pressing roller group 403 is rotatably connected to the oven 402, and the hot pressing roller group 403 includes a plurality of hot pressing rollers 404 rotatably connected to the oven 402, and the central axes of all the hot pressing rollers 404 are in the same horizontal plane. The vertical distance between the roller surface of the hot pressing roller 404 and the conveyor belt surface of the conveyor belt assembly 401 is equal to 0.998-1.0 times the height of the finished standard FPET Block. In the actual prototype design, the vertical distance between the roller surface of the hot pressing roller 404 and the conveyor belt surface of the conveyor belt assembly 401 is equal to 1.0 times the height of the finished standard FPET Block.
[0139] The spacing between adjacent hot pressing rollers 404 is 0.8-1.0 times the length of the finished standard FPET Block. In the actual prototype design, the spacing between adjacent hot pressing rollers 404 is 0.85 times the length of the finished standard FPET Block.
[0140] refer to Fig. 9 The hot pressing roller 404 is a fluororubber roller, and the roller surface temperature of the hot pressing roller 404 is equal to the temperature in the oven 402, that is, the surface temperature of the fluororubber roller is 88°C. The semi-finished FPET Block heat-treated by the FPET Block heat treatment subsystem 40 can eliminate internal stress, improve the mechanical properties and impact toughness of the finished standard FPET Block, facilitate the subsequent process to perform vertical cutting along the y-axis direction, improve the yield rate of the vertical cutting process along the y-axis direction, reduce the overall production cost of wind turbine blades, and facilitate the development and breakthrough of large-megawatt wind power generation products.
[0141] Embodiment A: The first PET layer 1 and the second PET layer 3 in the composite prepreg tape are PET thermal conductive films customized by Guangdong Shengyi Technology Co., Ltd., with a thermal conductivity of 0.75-0.80 W / m·K. The TPEE toughened and reinforced PET composite film in the composite prepreg tape is made of TPEE toughened and reinforced PET masterbatch. TPEE toughened and reinforced PET masterbatch is made of the following raw materials in percentage by mass: 35% TPEE resin LN5355HR, 5% compatibilizer-W5F polyester compatibilizer, 1% PET adhesion promoter 9041, 0.8% antioxidant 1024, 0.2% antioxidant 168, 0.8% anti-ultraviolet agent-UV-531, 1% lubricant-zinc stearate, 0.5% release agent PETSPT100, 5% filler (2000 mesh ultrafine calcium carbonate, 3mm long chopped glass fiber and zinc oxide whisker from Taian Senyang Composite Materials Co., Ltd. with a mass ratio of 16:3:1), and the balance is PET resin YS-Y01. The composite prepreg prepared as above is produced into classic PET foam composite core material for fan blades through a dedicated batch FPET Block production system. The depth of the tic-tac-toe grooves on the PET foam composite core material for fan blades is 23 mm, and the spacing between the grooves is 25 mm; the diameter of the holes punched in the PET foam composite core material for fan blades, i.e., the resin pouring holes, is 2 mm, and the spacing between adjacent resin pouring holes is 30 mm.
[0142] The performance parameters of the PET foam composite core material for classic wind turbine blades in Implementation A are as follows: Apparent density 115.1kg / m 3 , compression strength 1.73Mpa, compression modulus 108.1Mpa, shear strength 0.93Mpa, shear modulus 27.8Mpa, shear deformation 8.1%, tensile strength 2.9Mpa, tensile modulus 105.4Mpa.
[0143] The difference between Example B and Implementation A is that the TPEE toughened and reinforced PET composite film in the composite prepreg tape is made of thermally conductive TPEE toughened and reinforced PET masterbatch.
[0144] PEE toughened and reinforced PET masterbatch is made of the following raw materials in percentage by mass: 40% TPEE resin LN5355HR, 4% compatibilizer-W5F polyester compatibilizer, 1.5% PET adhesion promoter 9041, 0.8% antioxidant 1024, 0.2% antioxidant 168, 0.8% anti-ultraviolet agent-UV-531, 1% lubricant-zinc stearate, 0.5% release agent PETSPT100, 8wt% thermal conductive filler (ultrafine spherical alumina and carbon nanotubes in a mass ratio of 19:1), 2% reinforcing filler (2000 mesh ultrafine calcium carbonate, 3mm long chopped glass fiber and zinc oxide whisker from Taian Senyang Composite Materials Co., Ltd. in a mass ratio of 16:3:1), and the remainder is PET resin YS-Y01. The thermal conductivity of the PEE toughened and reinforced PET composite film prepared by using the above-mentioned PEE toughened and reinforced PET masterbatch is 0.8±0.05 W / m·K.
[0145] The performance parameters of the PET foam composite core material for classic wind turbine blades in Implementation Plan B are as follows: Apparent density 115.6kg / m 3 , compression strength 1.78Mpa, compression modulus 109.5Mpa, shear strength 0.95Mpa, shear modulus 28.4Mpa, shear deformation 7.8%, tensile strength 3.0Mpa, tensile modulus 106.7Mpa.
[0146] The standard inspection parameters of the classic PF-115 PET foam core material are as follows: apparent density 115+5kg / m 3 , compression strength ≥1.5Mpa, compression modulus ≥65Mpa, shear strength ≥0.75Mpa, shear modulus ≥20Mpa, shear deformation ≥5%, tensile strength ≥2.2Mpa, tensile modulus ≥85Mpa.
[0147] The control group is the PF-115 PET foam core material of Zhejiang Youwei New Materials Co., Ltd. The measured performance parameters of the PF-115 PET foam core material are as follows: apparent density 114.0kg / m 3 , compression strength ≥1.62Mpa, compression modulus 105Mpa, shear strength 0.83Mpa, shear modulus 26.0Mpa, shear deformation 8.3%, tensile strength 2.6Mpa, tensile modulus 99.0Mpa.
[0148] By comparing specific implementation schemes AB with the control group, it can be seen that the performance of the PET foamed composite core material for wind blades prepared in the present invention is comparable to that of the PF-115 PET foam core material in the control group (prior art), and the PET foamed composite core material for wind blades prepared in the present application can be mass-produced and continuously produced, reducing the total production cost of wind blades, and is conducive to the development and breakthrough of large-megawatt wind power generation products.
[0149] In summary, the preparation method provided by the present invention achieves the purpose of mass and continuous production of high-quality PET foam composite core materials for wind turbine blades through a dedicated mass FPET Block production system combined with a self-designed composite prepreg tape, effectively improving the production efficiency of the core material while improving the impact toughness and wind pressure impact resistance of wind turbine blades, reducing the total production cost of wind turbine blades, and facilitating the development and breakthrough of large-megawatt wind power generation products.
Claims
1. A method for preparing a PET foam composite core material for a fan blade, characterized in that: Here are the steps: Step 1: Preparation of PET foam substrate and composite prepreg coil: The composite prepreg tape coil comprises a first release paper (8), a plurality of composite prepreg tapes (10), and a second release paper (9), wherein the composite prepreg tape (10) is composited between the first release paper (8) and the second release paper (9); The composite prepreg tape comprises a first PET layer (1), a TPEE toughened and reinforced PET composite layer (2), and a second PET layer (3); the thickness of the first PET layer (1) and the second PET layer (3) are both 25-200 μm; the thickness of the TPEE toughened and reinforced PET composite layer (2) is 50-2000 μm; the TPEE toughened and reinforced PET composite layer (2) is filled with a fiber skeleton, and the fiber skeleton is 0° fiber and / or 90° fiber and / or plain woven fiber mesh; The 0° fiber includes at least one of glass fiber, carbon fiber, basalt fiber, aramid fiber, and ultra-high molecular weight polyethylene fiber distributed along the X-axis direction; The 90° fiber includes at least one of glass fiber, carbon fiber, basalt fiber, aramid fiber, and ultra-high molecular weight polyethylene fiber distributed along the Y-axis direction; The warp threads in the plain woven fiber mesh cloth include at least one of glass fiber, carbon fiber, basalt fiber, aramid fiber, and ultra-high molecular weight polyethylene fiber, and the weft threads in the plain woven fiber mesh cloth include at least one of glass fiber, carbon fiber, basalt fiber, aramid fiber, and ultra-high molecular weight polyethylene fiber; Step 2: First, a composite prepreg tape is hot-pressed on a PET foam substrate through a dedicated batch FPET Block production system, and then another PET foam substrate is hot-pressed on the composite prepreg tape, and the two PET foam substrates are hot-pressed and composited through the composite prepreg tape to form a double-stacked PET foam board; Step 3, the two stacked PET foam boards are laminated at least sequentially from bottom to bottom on the composite prepreg tape / PET foam substrate / … / composite prepreg tape / PET foam substrate / PET foam substrate to form n+1 stacked PET foam boards, i.e., semi-finished FPET Block; Step 4, heat-treating the semi-finished FPET Block to obtain a finished standard FPET Block; Step 5: The standard FPET Block is vertically cut along the y-axis direction to obtain a PET foam composite core material substrate, and the obtained PET foam composite core material substrate is grooved, punched, edge cut, flattened, and polished to obtain a finished PET foam composite core material.
2. The method for preparing a PET foam composite core material for a fan blade according to claim 1, characterized in that: The preparation method of the composite prepreg coil described in step 1 is as follows: S1, preparation of TPEE toughened and reinforced PET composite film; the TPEE toughened and reinforced PET composite layer is prepared by extrusion melting, casting, stretching and cooling of TPEE toughened and reinforced PET masterbatch; S2, preparation of composite prepreg tape: first fix the fiber skeleton in a forming mold, then apply the TPEE toughened and reinforced PET composite film to the upper and lower surfaces of the fiber skeleton respectively, and obtain the TPEE toughened and reinforced PET composite sheet containing the fiber skeleton by hot pressing and compounding, that is, the TPEE toughened and reinforced PET composite layer (2), then cover the first PET film on one surface of the TPEE toughened and reinforced PET composite sheet, and cover the second PET film on the other surface of the TPEE toughened and reinforced PET composite sheet, and obtain the composite prepreg tape containing the fiber skeleton by hot pressing and compounding, and cut and trim it for use; S3, preparation of composite prepreg tape roll: firstly compound a plurality of composite prepreg tapes on a second release paper, with the intervals between adjacent composite prepreg tapes on the second release paper being equal, and then compound the first release paper on the surface of the composite prepreg tape facing away from the composite prepreg tape, and then roll up to obtain a finished composite prepreg tape roll.
3. The method for preparing a PET foam composite core material for a fan blade according to claim 2, characterized in that: The TPEE toughened and reinforced PET masterbatch is made of the following raw materials in percentage by mass: 25-40% TPEE resin, 3-6% compatibilizer, 0.5-3% PET adhesion promoter, 0.8-2% antioxidant, 0.5-1.0% anti-ultraviolet agent, 0.5-1.0% lubricant, 0.5-1.0% release agent, 0-15% filler, and the balance is PET resin; The TPEE resin has a melting temperature of 195-220° C., a bending elastic modulus ≥180 MPa, a tensile strength ≥24 MPa, and a Shore hardness of 45-55D; The compatibilizer is at least one of W5D polyester compatibilizer, W5F polyester compatibilizer, W5A polyester compatibilizer, and cyclic maleic anhydride grafted product; The PET adhesion promoter is at least one of Y-1900-1PET adhesion promoter, F-1 PET adhesion promoter, ADK adhesion promoter, 9041 adhesion promoter, HYCM-7555 adhesion promoter, epoxy silane, amino silane, isocyanate silane, and methacryloxy silane; The antioxidant is an organic phosphite antioxidant and / or an organic phenol antioxidant; The anti-ultraviolet agent is at least one of a benzotriazole ultraviolet absorber, an oxalic acid amide light stabilizer, a triazine light stabilizer, and a hindered amine light stabilizer; The filler includes a thermally conductive filler and / or a reinforcing filler; The reinforcing filler includes at least one of calcium carbonate, barium sulfate, kaolin, montmorillonite, silicon powder, titanium dioxide, mica powder, quartz powder, shell powder, chopped carbon fiber, chopped glass fiber, and inorganic whiskers; The thermal conductive filler comprises at least one of aluminum oxide, aluminum nitride, silicon nitride, titanium nitride, boron nitride, silicon carbide, titanium carbide, and zirconium carbide, and at least one of graphene and carbon nanotubes; The PET resin is bottle-grade polyester chips, and the bottle-grade polyester chips are any one of Wankai WK801, Sanfangxiang CZ-318, Hainan Yisheng-YS-Y01, Pan Asia FY1004, and China Resources CR-8863.
4. The method for preparing a PET foam composite core material for a fan blade according to claim 3, characterized in that: The filler in the TPEE toughened and reinforced PET masterbatch consists of a thermally conductive filler and a reinforcing filler. The thermally conductive filler forms a three-dimensional network thermally conductive structure in the TPEE toughened and reinforced PET composite film. The thermal conductivity of the TPEE toughened and reinforced PET composite film is 0.5-3.0 W / m·K.
5. The method for preparing a PET foam composite core material for a fan blade according to claim 3, characterized in that: The first PET film and the second PET film contain thermally conductive fillers, and the thermally conductive fillers form a three-dimensional network thermally conductive structure in the first PET film or the second PET film. The thermal conductivity of the first PET film and the second PET film is 0.5-3.0W / m·K; the thermal conductivity of the composite prepreg tape as a whole is 0.5-3.0W / m·K; the thermally conductive filler includes at least one of aluminum oxide, aluminum nitride, silicon nitride, titanium nitride, boron nitride, silicon carbide, titanium carbide, and zirconium carbide, and at least one of graphene and carbon nanotubes.
6. The method for preparing a PET foam composite core material for wind turbine blades according to claims 4 and 5, characterized in that: The thermal conductive filler in the TPEE toughened and reinforced PET masterbatch is composed of ultrafine spherical alumina and carbon nanotubes in a mass ratio of (18-19): (1-2); the reinforcing filler in the TPEE toughened and reinforced PET masterbatch is composed of ultrafine calcium carbonate and chopped glass fiber in a mass ratio of (4-7): 1; or the reinforcing filler in the TPEE toughened and reinforced PET masterbatch is composed of ultrafine calcium carbonate, chopped glass fiber and inorganic whisker in a mass ratio of (14-17): (2-4): 1; the thermal conductive filler in the first PET film and the second PET film is also composed of ultrafine spherical alumina and carbon nanotubes in a mass ratio of (18-19): (1-2).
7. The method for preparing a PET foam composite core material for a fan blade according to claim 3, characterized in that: The TPEE toughened and reinforced PET masterbatch is made of the following raw materials in percentage by mass: 34-36% of TPEE resin LN5355HR, 4-6% of compatibilizer-W5F polyester compatibilizer, 0.8-1.2% of PET adhesion promoter 9041, 0.70-0.85% of antioxidant 1024, 0.15-0.2% of antioxidant 168, 0.70-0.80% of anti-ultraviolet agent UV-531, 0.8-1.0% of zinc stearate, 0.4-0.6% of release agent PETSPT100, 4-6% of filler, and the balance is PET resin YS-Y01; the filler is composed of 2000-mesh ultrafine calcium carbonate, chopped glass fiber and zinc oxide whisker in a mass ratio of 16:3:
1.
8. The method for preparing a PET foam composite core material for a fan blade according to claim 3, characterized in that: The TPEE toughened and reinforced PET masterbatch is made of the following raw materials in percentage by weight: 38-40% of TPEE resin LN5355HR, 3.8-4% of compatibilizer-W5F polyester compatibilizer, 1.4-1.5% of PET adhesion promoter 9041, 0.75-0.8% of antioxidant 1024, 0.15-0.2% of antioxidant 168, 0.7-0.8% of anti-ultraviolet agent UV-531, 0.8-1% of zinc stearate, 0 .4-0.6% of release agent PETSPT100, 8-10wt% of thermal conductive filler, 2-4% of reinforcing filler, and the balance is PET resin YS-Y01; the thermal conductive filler is composed of ultrafine spherical alumina and carbon nanotubes in a mass ratio of 19:1; the reinforcing filler is composed of 2000 mesh ultrafine calcium carbonate and zinc oxide whiskers in a mass ratio of 19:1; the thermal conductivity of the TPEE toughened and reinforced PET masterbatch is 0.75-0.95W / m·K.
9. The method for preparing a PET foam composite core material for a fan blade according to claim 3, characterized in that: The preparation method of the TPEE toughened and reinforced PET composite film is as follows: S1. Evenly mix the accurately measured TPEE resin, compatibilizer, PET adhesion promoter, antioxidant, UV resistant agent, lubricant, release agent, filler and PET resin and place them in a screw extruder for melt extrusion, wire drawing, cooling, granulation and drying to obtain TPEE toughened and reinforced PET masterbatch; S2. The TPEE toughened and reinforced PET masterbatch is placed in a screw extruder for melt extrusion, casting, biaxial stretching, shaping, and cooling to obtain a TPEE toughened and reinforced PET composite unit film. The film thickness of the obtained TPEE toughened and reinforced PET composite unit film can be obtained by adjusting the transverse stretching coefficient and the longitudinal stretching coefficient in the biaxial stretching parameters to obtain a TPEE toughened and reinforced PET composite film with a thickness of 50-2000μm.
10. The method for preparing a PET foam composite core material for a fan blade according to claim 3, characterized in that: In the fourth step, the semi-finished FPET Block is heat treated, and the heat treatment parameters are as follows: heat treatment at 80-90° C. for 200-400 seconds, and cooling to room temperature to obtain the finished standard FPET Block.